The Revitalization of the Creed Theory in Indonesian Islamic Family Law: Measuring the Limits of Legal Tolerance toward Interfaith Marriage - Fiki Rahmawati; Navila Ash Shofwa Kamila Farid; Farahin, Salma (Tebuireng: Journal of Islamic Studies and Society, 2026)
This study analyzes creed theory as the philosophical foundation for implementing Islamic law in Indonesian family law and examines the limits of legal tolerance toward interfaith marriage. The issue arises from tension between Article 2(1) of Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law, which prohibit interfaith marriage, and the continuing practice of such marriages through various legal channels, including district court determinations. Using a normative legal method with legislative, conceptual, and historical approaches, this research employs qualitative interpretive analysis of relevant legal materials. The findings indicate that creed theory remains relevant as an epistemological framework linking Islamic theological principles with Indonesia’s positive legal system. Its influence is reflected in Article 8(f) of the Marriage Law, Articles 40(c) and 44 of the Compilation of Islamic Law, and reinforced by Constitutional Court Decisions Number 68/PUU-XII/2014 and Number 24/PUU-XX/2022. The study also finds that, prior to Supreme Court Circular Letter Number 2 of 2023, inconsistencies emerged among district courts due to the absence of clear and uniform legal norms. As a result, some judges approved applications related to interfaith marriage registration. The Circular Letter seeks to reduce these disparities by reaffirming restrictions on interfaith marriage and narrowing interpretive differences among judges. However, its nonbinding character leaves unresolved questions concerning harmonization with the Population Administration Law and legal certainty. The study concludes that Indonesia's legal tolerance recognizes religious diversity but not marriages conflicting with religious law. It therefore recommends strengthening regulations, improving judicial capacity, and enhancing education nationwide.